Opoziční smlouvy „za kopečky“ I.: Byl pakt ČSSD a ODS z let 1998–2002 demokratickou deviací? - Kopeček, Lubomír (Středo Evropské politické studie, 2013)
After the 1998 general elections to the Chamber of Deputies of the Czech Republic, the largest party, the Social Democratic Party (ČSSD), formed a minority government. The origin and existence of this government was enabled by an agreement with the second largest formation, the Civic Democratic Party (ODS). What was then known as the Opposition Agreement became the subject of considerable debate. The paper analyses the Opposition Agreement in comparison with other minority governments with external support, be they governments formed on the basis of ad hoc agreements or complex ones. The text looks in detail at government practice in Denmark, Sweden, New Zealand, and Italy at the time of the Historic Compromise; this is then used as a context for outlining the specifics of the Czech case. The paper highlights not only the Opposition Agreement between the Social Democrats and the Civic Democratic Party and the later Toleration Patent, which even deepened the cooperation between these two parties, but also the frequent ad hoc legislative coalitions which the minority government was able to form. An additional aim of the paper is to outline foreign analogies to the potential future single-party minority government of the Czech Social Democrats supported by the Communists. Because of its considerable length, the text is divided into two parts; the first part is printed in this volume.